Movement-related cortical potentials in paraplegic patients: abnormal patterns and considerations for BCI-rehabilitation - Xu, Ren; Jiang, Ning; Vuckovic, Aleksandra; Hasan, Muhammad; Mrachacz-Kersting, Natalie; Allan, David; Fraser, Matthew; Nasseroleslami, Bahman; Conway, Bernie; Dremstrup, Kim; Farina, Dario (Frontiers in Neuroengineering, 2014)
Non-invasive EEG-based Brain-Computer Interfaces (BCI) can be promising for the motor neuro-rehabilitation of paraplegic patients. However, this shall require detailed knowledge of the abnormalities in the EEG signatures of paraplegic patients. The association of abnormalities in different subgroups of patients and their relation to the sensorimotor integration are relevant for the design, implementation and use of BCI systems in patient populations. This study explores the patterns of abnormalities of movement related cortical potentials (MRCP) during motor imagery tasks of feet and right hand in patients with paraplegia (including the subgroups with/without central neuropathic pain and complete/incomplete injury patients) and the level of distinctiveness of abnormalities in these groups using pattern classification. The most notable observed abnormalities were the amplified execution negativity and its slower rebound in the patient group. The potential underlying mechanisms behind these changes and other minor dissimilarities in patients’ subgroups, as well as the relevance to BCI applications, are discussed. The findings are of interest from a neurological perspective as well as for BCI-assisted neuro-rehabilitation and therapy.